Easby-Smith family papers
Chiefly correspondence of William Russell Smith with his wife, Wilhelmine, relating to the seccession of Alabama and to Confederate congressional affairs. Also includes correspondence (1837-1848) of Smith's father-in-law, William Easby, with Millard Fillmore and others.
William Russell Smith (1815-1896) was a U.S. and Confederate representative from Alabama and an officer in the 26th Alabama Volunteers, whose third wife was Wilhelmine M. Easby, daughter of William Easby.
Collection material in English.
Keywords: Easby, William, -- 1791-1854. -- Correspondence; Smith, Wilhelmine M. Easby. -- Correspondence; Smith, William Russell, -- 1815-1896. -- Correspondence; Fillmore, Millard, -- 1800-1874 -- Correspondence; Easby family; Smith family; Confederate States of America. -- Army. -- Alabama Infantry Regiment, 26th.; Confederate States of America. -- Congress; Secession; Alabama -- History -- Civil War, 1861-1865.